Amblyceps cerinum, a new catfish (Teleostei: Amblycipitidae) from northeastern India - Ng, Heok Hee; Wright, Jeremy J. (Zootaxa, 2010)
Amblyceps cerinum, a new South Asian amblycipitid catfish species, is described from the Brahmaputra River drainage in northern West Bengal, India. The new species can be distinguished from congeners in having a combination of upper jaw longer than lower, incomplete lateral line terminating beneath posterior insertion of dorsal fin, length of adipose-fin base 32.4–38.3% SL, caudal peduncle length 21.9–24.5% SL, caudal peduncle depth 9.2–11.2% SL, 41–44 postWeberian vertebrae, posterior end of adipose fin separated from dorsal procurrent caudal-fin rays by distinct notch, and truncate caudal fin. The taxonomic status of A. tenuispinis is also discussed and a neotype designated for this species.